2014
DOI: 10.1007/s13105-014-0318-3
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin confers protection against oxidative stress through upregulation of Nrf2 target genes in cardiomyoblast cells

Abstract: Cardiovascular diseases are the major health concern and the leading cause of death. Numerous studies have shown that oxidative stress stimuli have been incriminated in the pathogenesis of both acute and chronic heart disease. Though it is well known that bioflavonoids protect cells against reactive oxygen species (ROS)-induced damage, the molecular mechanisms involved are uncertain. Understanding the possible intracellular signaling pathways triggered by flavonoids will help to overcome the cardiac diseases r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 24 publications
1
37
0
Order By: Relevance
“…This indicates that naringenin exerts antiapoptotic effect, which can be attributed to its anti-inflammatory, antioxidant, and antinitrosative properties. Similarly, other studies showed that caspase-3 and cell apoptosis were significantly inhibited by naringenin [32,33] .…”
Section: Discussionmentioning
confidence: 56%
“…This indicates that naringenin exerts antiapoptotic effect, which can be attributed to its anti-inflammatory, antioxidant, and antinitrosative properties. Similarly, other studies showed that caspase-3 and cell apoptosis were significantly inhibited by naringenin [32,33] .…”
Section: Discussionmentioning
confidence: 56%
“…In agreement with previous reports[13,15,50-53], CCl 4 decreased GPx activity in this study. NAR cotreatment partially prevented the decrement in GPx activity, probably by up regulating its expression through Nrf2 modulation[15,40,43,44-47,50], providing another mechanism to fight oxidative stress induced by CCl 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed NGN (50 µM) protected H9c2 cardiomyocytes from H 2 O 2 -mediated cells death, reduced lipid peroxidation and increased the activity of anti-oxidant enzymes [81]. …”
Section: In Vitro Effects Of Polyphenols Against Oxidative Stress-mentioning
confidence: 99%